5.7 GHz on-chip antenna/RF CMOS transceiver for wireless sensor networkS - Carmo, João Paulo Pereira (2008)
This paper describes a chip-size antenna for operation at 5.7 GHz, assembled with a low-power, low-voltage RF CMOS transceiver, fabricated in UMC RF CMOS 0.18 μm process. Measurements shown a patch antenna with the central frequency of 5.705 GHz, a bandwidth of 90 MHz at −10 dB of return loss, a directive gain of 0.3 dB, with an efficiency of 18%, and a transceiver with a measured total power consumption of 23 mW. This microsystem is intended for the use in each wireless node of a wireless sensor network mounted in a wireless electronic shirt, that monitors the cardio-respiratory function and posture.